Modularity in design and modularity in production: an analysis through a theoretical framework and a field investigation in two automakers - Kubota, Flávio Issao (2017)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia de Produção, Florianópolis, 2017.